HOW TO FLY A HORSE : THE SECRET HISTORY OF CREATION, INVENTION, AND DISCOVERY - Ashton, Kevin
Inspiring and empowering, this journey behind the scenes of humanity's greatest creations reveals the surprising way we make something new. What do Thomas Jefferson's ice cream recipe, Coca Cola, and Chanel No. 5 have in common? They all depended on a n